2021
DOI: 10.1161/circulationaha.120.046290
|View full text |Cite|
|
Sign up to set email alerts
|

PCSK9 (Proprotein Convertase Subtilisin/Kexin 9) Enhances Platelet Activation, Thrombosis, and Myocardial Infarct Expansion by Binding to Platelet CD36

Abstract: Background: Proprotein convertase subtilisin/kexin 9 (PCSK9), mainly secreted by the liver and released into the blood, elevates plasma low-density lipoprotein (LDL) cholesterol by degrading LDL receptor. Pleiotropic effects of PCSK9 beyond lipid-metabolism have been shown. However, the direct effects of PCSK9 on platelet activation and thrombosis, as well as the underlying mechanisms, still remain unclear. Methods: We detected the direct effects of PCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
189
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(196 citation statements)
references
References 57 publications
7
189
0
Order By: Relevance
“…Recent studies revealed that PCSK9 inhibitors prevent CVD through mechanisms other than only reducing LDL-C levels. Several new effects of PCSK9 on diseases, such as insulin resistance and thrombus, have been revealed 13 , 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies revealed that PCSK9 inhibitors prevent CVD through mechanisms other than only reducing LDL-C levels. Several new effects of PCSK9 on diseases, such as insulin resistance and thrombus, have been revealed 13 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, most studies on the PCSK9 gene were focused on several polymorphisms, such as E670G or R46L, and the findings suggested that the PCSK9 gene was significantly associated with LDL-C levels and CAD 10 12 . Recently, an increasing number of studies have implied that PCSK9 might affect CAD beyond its effects on lipids and that it also interacts with cardiovascular risk factors, such as insulin resistance 13 , 14 , inflammation 15 , platelet activation 16 , and thrombosis 17 . However, these multieffects of PCSK9 are still unclear, and whether there are novel genetic targets of PCSK9 that could be applied to therapy for atherosclerotic cardiovascular disease (ASCVD) with safer, more efficient, and pleiotropic effects requires further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, PCSK9 also downregulates other receptors in the LDLR family [79,80], and binds the scavenger receptor, CD36, concurrent with thrombosis [97,99]. Thus, the effect of increasing LDLR in the athero-protective effects of PCSK9, beyond lowering serum LDL concentration, is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…General upregulation of the LDLR receptor function through inhibition of PCSK9 have been reported to bene t against coronary artery disease [97,98]. Notwithstanding, PCSK9 also downregulates other receptors in the LDLR family [79,80], and binds the scavenger receptor, CD36, concurrent with thrombosis [97,99]. Thus, the effect of increasing LDLR in the athero-protective effects of PCSK9, beyond lowering serum LDL concentration, is more complex.…”
Section: Discussionmentioning
confidence: 99%